Severe vitamin D deficiency is associated with frequently observed diseases in medical inpatients. Issue 5 (6th February 2014) - Marra, A.; Leoncini, G.; Mussap, M.; Bovio, M.; Nazzari, E.; Giusti, M.; Minuto, F.; Murialdo, G.; Ameri, P.
Summary Introduction Vitamin D deficiency consequences may go beyond altered calcium homeostasis and musculoskeletal disease. Medical inpatients are often vitamin D‐deficient, but little information is available about the relation of vitamin D status with extra‐skeletal disorders in this population. Methods We analysed the relationship between the concentrations of 25‐hydroxyvitamin D [25(OH)D], the marker of vitamin D status, and the conditions most commonly causing admission in 115 consecutive medical inpatients. Results Sixty‐five subjects (56.5%) had severe vitamin D deficiency [25(OH)D < 8 ng/ml]. Age (β = −0.35, p = 0.01) and hepatic disease (β = −0.21, p = 0.02) were significant correlates of 25(OH)D levels. Compared with patients with ≥ 8 ng/ml 25(OH)D, those with < 8 ng/ml 25(OH)D had significantly higher parathyroid hormone (PTH) concentrations [123 (92.7–208.2) ng/l vs. 88 (68.5–129.5) ng/l, p < 0.001], were significantly more likely to have arterial hypertension (OR 2.76, 95% CI 1.16–6.58), heart failure (HF) (OR 2.49, 95% CI 1.14–5.47), cerebrovascular disease (OR 3.23, 95% CI 1.41–7.39), and infections (OR 2.44, 95% CI 1.02–5.87), and stayed in hospital significantly longer (10 days vs. 7.5 days, p = 0.01). Only the probability of having an infection remained significantly higher in cases with severe vitamin D deficiency after adjustment for age (OR 2.41, 95% CI 1.03–5.68) and persisted after further correcting for presence of hepatic disease and PTH values (OR 2.66, 95% CI 1.03–6.88). A significant association between PTH and HF (OR 2.32, 95% CI 1.05–5.09) and length of hospitalisation (β = 0.22, p = 0.04) emerged in the fully adjusted regression models. Conclusions Severe vitamin D deficiency is associated with commonly presenting extra‐skeletal diseases in medical inpatients. With the exception of infections, this association is mainly driven by age. Additional studies are needed to determine whether vitamin D testing on admission may help stratifying specific categories of patients by clinical severity.